Fatigue behavior of thick composite laminates under flexural loading. (15th September 2018) - Hamidi, H.; Xiong, W.; Hoa, S.V.; Ganesan, R.
Abstract: Most of the existing work on fatigue of long fiber composite laminates approach the problem from the material point of view. These works have also been mainly on thin laminates. This is because the laminates (particularly unidirectional laminates) are considered to be homogeneous and uniform. This may or may not be true because of the heterogeneous nature of the composite (consisting of fibers and matrix and interface), and the significant variability which gives rise to random spatial variation in the properties. A composite laminate is actually both a structure and a material. For thin laminates, the structural aspect is usually scanned over and only the material aspect is focused on. This gives rise to the expectation that the laminate should behave as a material (with good homogeneity and with little variability). This has resulted in failure of many failure criteria. The importance of the structural aspect is more evident for the case of thick laminates, subjected to flexural loading while being constrained by bolts. To study the fatigue behavior of such materials (and structures), both the structural aspects and material aspects must be taken into consideration. This is the subject of study of this paper. It examines the behavior of 80-layer thick unidirectional glass/epoxy laminates subjected to flexural loads while being constrained by bolts. Both theoretical and experimental studies are carried to validate each other. The theoretical part consists first of structural analysis which provides the locations of potential failure. This is followed by the application of fatigue failure criteria at these locations. Good agreement is obtained between the experimental and theoretical results.